Changing perceptions of conflict: The beneficiaries of Intra-ethnic conflict among the Abakuria Community, Kenya - Kungu, David Mwangi; Omari, Risper Kerubo (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Conflict in many parts of the world has become part of people’s life resulting in massive deaths, displacement of people and trail of destruction to property leading to manmade disasters. In Kenya, conflict is experienced as warring groups engage in armed and non-armed conflicts. A peculiar case is that of the Abakuria ethnic group, where inter-clan conflicts have become perpetual. The mechanisms used in managing the conflict have been both inadequate and ineffective as the conflicts keep recurring. It is on this backdrop that this study aimed at evaluating beneficiaries to the conflict with a view of establishing the root causes of intra-ethnic conflict. The study employed descriptive survey, ethnography and explanatory research designs. The target population for the study was 52,338 comprising of members of the indigenous conflict management systems, members of provincial administration, local and international Non-governmental Organizations, Community Based Organizations, Faith Based Organizations, community policing members, members of peace committees, civic leaders, District security team, warriors and community members/victims to the conflict. From the target population, a sample 638 was selected using purposive sampling, stratified sampling, transect walk and snowball sampling techniques. Data were collected using questionnaires, in-depth interviews and focus group discussion. Quantitative data generated from the study were analysed descriptively while qualitative data were analysed following the five steps of thematic data analysis: transcription, open coding, axial coding, selecting codes and formation of themes. The study established that there were several categories of beneficiaries to intra-ethnic conflict including government officials, traders, consumers, households, politicians and members of the traditional institutions. The study recommends that there is need to enlighten the community on the negative effects of intra-ethnic conflict. In addition, cartel of beneficiaries of such conflict who work to catalyse the conflict for their own benefit should be severely punished.